Immunomodulatory Protective Effects of Rb9 Cyclic-Peptide in a Metastatic Melanoma Setting and the Involvement of Dendritic Cells - Machado, Fabrício C.; Girola, Natália; Maia, Vera S. C.; Bergami-Santos, Patrícia C.; Morais, Alice S.; Azevedo, Ricardo A.; Figueiredo, Carlos R.; Barbuto, José A. M.; Travassos, Luiz R. (Frontiers in Immunology, 2020)
The cyclic VHCDR3-derived peptide (Rb9) from RebMab200 antibody, directed to a NaPi2B phosphate-transport protein, displayed anti-metastatic melanoma activity at 50–300 μg intraperitoneally injected in syngeneic mice. Immune deficient mice failed to respond to the peptide protective effect. Rb9 induced increased CD8+ T and low Foxp3+ T cell infiltration in lung metastases and high IFN-γ and low TGF-β in lymphoid organs. The peptide co-localized with F-actin and a nuclear site in dendritic cells and specifically bound to MIF and CD74 in a dot-blot setting. Murine bone-marrow dendritic cells preincubated with Rb9 for 6 h were treated with MIF for short time periods. The modulated responses showed stimulation of CD74 and inhibition of pPI3K, pERK, and pNF-κB as compared to MIF alone. Rb9 in a melanoma-conditioned medium, stimulated the M1 type conversion in bone marrow-macrophages. Functional aspects of Rb9 in vivo were studied in therapeutic and prophylactic protocols using a melanoma metastatic model. In both protocols Rb9 exhibited a marked anti-melanoma protection. Human dendritic cells were also investigated showing increased expression of surface markers in response to Rb9 incubation. Rb9 either stimulated or slightly inhibited moDCs submitted to inhibitory (TGF-β and IL-10) or activating (LPS) conditions, respectively. Lymphocyte proliferation was obtained with moDCs stimulated by Rb9 and tumor cell lysate. In moDCs from cancer patients Rb9 exerted immunomodulatory activities depending on their functional status. The peptide may inhibit over-stimulated cells, stimulate poorly activated and suppressed cells, or cause instead, little phenotypic and functional alterations. Recently, the interaction MIF-CD74 has been associated to PD-L1 expression and IFN-γ, suggesting a target for melanoma treatment. The effects described for Rb9 and the protection against metastatic melanoma may suggest the possibility of a peptide reagent that could be relevant when associated to modern immunotherapeutic procedures.